"Do you know chronic illness?" The game - Lahti, Johanna; Zaragatzky, Arielle (My University, 2025)
In this thesis, we investigate how games can be used to raise awareness about living with a chronic illness, specifically Ehlers-Danlos syndrome (EDS). We conducted a literature review, followed by a survey and interview with people with EDS. With the gathered information, we developed a visual novel where the player controls the main character, who has EDS. In the game, the player has to make choices while being careful with their health. Multiple rounds of user testing were done throughout the development, and the feedback was analysed. After the final user tests, we found several game elements that seemed to contribute to the effectiveness of raising awareness for EDS. Among these were the accuracy of the portrayal of EDS, the game asset quality, game mechanics and controls, variation in gameplay, and emotional experiences.
Keywords: Computer, science, computer science, engineering, interaction design, games, project, thesis.